Analysing the determinants of higher education systems' performance–a structural equation modelling approach. (5th August 2019) - Agasisti, Tommaso; Bertoletti, Alice
Abstract: This article deals with the relationships between the performance of higher education systems (HESs) and their potential determinants. The research employed data relating to twenty-nine European countries, within a time span of 15 years. The empirical work is based on a conceptual framework that has been tested through Structural Equation Modelling. The data was selected from a novel data set that we have built by gathering HES indicators from the major international databases. Among the more noteworthy results, we found no statistically significant correlation between graduation rates and research performance. Additionally, we found a moderate effect of public expenditure on HES performance. The article addresses the issue of the lack of a comprehensive set of systemic indicators for HES performance, providing a holistic picture of the relationship between HES determinants and performance, which, in turn, could help to provide an adequate evaluation of the policies in the field of higher education.